Comparison of Heritability Estimation and Linkage Analysis for Multiple Traits Using Principal Component Analyses. Issue 3 (April 2016) - Liang, Jingjing; Cade, Brian E.; Wang, Heming; Chen, Han; Gleason, Kevin J.; Larkin, Emma K.; Saxena, Richa; Lin, Xihong; Redline, Susan; Zhu, Xiaofeng
ABSTRACT: A disease trait often can be characterized by multiple phenotypic measurements that can provide complementary information on disease etiology, physiology, or clinical manifestations. Given that multiple phenotypes may be correlated and reflect common underlying genetic mechanisms, the use of multivariate analysis of multiple traits may improve statistical power to detect genes and variants underlying complex traits. The literature, however, has been unclear as to the optimal approach for analyzing multiple correlated traits. In this study, heritability and linkage analysis was performed for six obstructive sleep apnea hypopnea syndrome (OSAHS) related phenotypes, as well as principal components of the phenotypes and principal components of the heritability (PCHs) using the data from Cleveland Family Study, which include both African and European American families. Our study demonstrates that principal components generally result in higher heritability and linkage evidence than individual traits. Furthermore, the PCHs can be transferred across populations, strongly suggesting that these PCHs reflect traits with common underlying genetic mechanisms for OSAHS across populations. Thus, PCHs can provide useful traits for using data on multiple phenotypes and for genetic studies of trans‐ethnic populations.